2011
DOI: 10.2320/matertrans.m2011007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature, Basiscity and Particle Size on MnO Reduction

Abstract: The aim of this work is to study MnO reduction by solid carbon. The influence of size of carbon particles, slag basicity, and bath temperature on MnO reduction was investigated. Fine Manganese ore particles were used as a source of MnO. Three sizes of carbon particles were used; 0.230 mm, 0.162 mm and 0.057 mm, binary basicity of 1 and 1.5 and temperatures of 1550, 1550 and 1600 C. Curves were drawn for Mn content in the bath as a function of time and temperature for the several studied parameters. The MnO red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
2
1
Order By: Relevance
“…An effect may also be observed of adding quartz and lime to a charge, i.e., weight loss increases with an increase in basicity. However, with T = 1400°C weight apparently decreased with an increase in basicity of both ores, and this fact is unexpected and difficult to explain since it does not agree with results of previous re-search [5,7,8] in which it was detected that an increase in basicity facilitated MnO reduction.…”
contrasting
confidence: 81%
See 1 more Smart Citation
“…An effect may also be observed of adding quartz and lime to a charge, i.e., weight loss increases with an increase in basicity. However, with T = 1400°C weight apparently decreased with an increase in basicity of both ores, and this fact is unexpected and difficult to explain since it does not agree with results of previous re-search [5,7,8] in which it was detected that an increase in basicity facilitated MnO reduction.…”
contrasting
confidence: 81%
“…Reduction of MnO from manganese ore of a deposit in Erzincan in the range 1550-1600°C using slag basicity from 1 to 1.5 has been studied in [5]. It has been established that the degree of MnO reduction by solid carbon increases with an increase in slag basicity.…”
mentioning
confidence: 99%
“…The particle size of the raw material is an important factor affecting the reduction of the briquettes. Previous studies have shown that the particle size has an important influence on the strength and the reduction [7,8], the reduction kinetics [9][10][11][12] of iron ore-coal composite briquettes, and the rates of the MnO reduction [13]. However, few studies had been done on the effect of particle size of nickel slag during coal-based reduction.…”
Section: Introductionmentioning
confidence: 99%